PHYSICAL AND TOTAL QUALITY OF SUI WU'U TOTAL ACID BACTERIA PRESERVED WITH CORN FLOUR (AMYLUM MAYDIS) - E., Febrianti; Miwada, I N. S.; Lindawati, S. A. (Jurnal Peternakan Tropika, 2021)
This research was conducted to determine the results of the physical quality test and the total lactic acid bacteria of pork L andrace preserved by the traditional preservation method of the Ngada community, East Nusa Tenggara Province. The research was conducted from September to November 2020 at the Laboratory of Animal Product Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. In this study, the experimental design used was a completely randomized design (CRD) with three treatments and five replications.  The three treatments were: pork Landrace which was preserved with the addition of 0.5 kg of corn flour (P1), Landrace pork which was preserved with the addition of 1 kg of corn flour (P2), pork Landrace which was preserved with the addition of corn flour 1.5 kg (P3).  The variables observed were pH value, cooking losses, water holding capacity and total lactic acid bacteria (LAB).  The results showed that the addition of corn flour 0.5 kg, 1 kg, 1.5 kg to the preservation of sui wu'u obtained pH results of 4.19 - 4.18; water holding capacity 28.29% - 20.59%; cooking shrinkage 13.37% - 10.17%; lactic acid bacteria 2.7 x 10 7    cfu/g – 1.0 x 10 8   cfu/g. From treatment P1 to P3, the results were not significantly different (P>0.05), which means that the effectiveness of using corn flour was sufficient in treatment P1 with the addition of 0.5 kg in the preservation method sui wu'u .   Key word: Sui wu’u ,  corn flou r,  physical quality Pork Landrace, lactic acid bacter i